Enhancing calmodulin binding to ryanodine receptor is crucial to limit neuronal cell loss in Alzheimer disease - Yoshihide Nakamura (Nature Portfolio, 2021)
Abstract Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive neuronal cell loss. Recently, dysregulation of intracellular Ca2+ homeostasis has been suggested as a common proximal cause of neural dysfunction in AD. Here, we investigated (1) the pathogenic role of destabilization of ryanodine receptor (RyR2) in endoplasmic reticulum (ER) upon development of AD phenotypes in App NL-G-F mice, which harbor three familial AD mutations (Swedish, Beyreuther/Iberian, and Arctic), and (2) the therapeutic effect of enhanced calmodulin (CaM) binding to RyR2. In the neuronal cells from App NL-G-F mice, CaM dissociation from RyR2 was associated with AD-related phenotypes, i.e. Aβ accumulation, TAU phosphorylation, ER stress, neuronal cell loss, and cognitive dysfunction. Surprisingly, either genetic (by V3599K substitution in RyR2) or pharmacological (by dantrolene) enhancement of CaM binding to RyR2 reversed almost completely the aforementioned AD-related phenotypes, except for Aβ accumulation. Thus, destabilization of RyR2 due to CaM dissociation is most likely an early and fundamental pathogenic mechanism involved in the development of AD. The discovery that neuronal cell loss can be fully prevented simply by stabilizing RyR2 sheds new light on the treatment of AD.